2020
DOI: 10.1021/acs.nanolett.0c01394
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the Side Reaction by a Selective Blocking Layer to Enhance the Performance of Si-Based Anodes

Abstract: Building a stable solid electrolyte interphase (SEI) is an effective method to enhance the performance of Si-based materials. However, the general strategy ignores the severe side reaction that originates from the penetration of the fluoride anion which influences the stability of the SEI. In this work, an analytical method is established to study the chemical reaction mechanism between the silicon and electrolyte by combining X-ray diffraction (XRD) with mass spectrometry (MS) technology. Additionally, a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…In principle, downsizing bulk Si to the nanoscale (below the critical value) can prevent crack propagation due to the reduced strain energy stored from electrochemical reactions, thus improving structural stability and cycling lifespan. Since the pioneering work of Si nanowires as an anode in 2008, a wide range of nanostructures, including hollow nanospheres, nanotubes, and nanosheets, have been explored to avoid mechanical fracture. Furthermore, combining nanostructures with some powerful concepts involving surface coating, void engineering, and compositing (with inactive or conductive medium ) has been demonstrated to be successful in building smart electrode structures, which can achieve exceptional performances with outstanding high specific capacity and long-term cycle life (Figure A). , …”
mentioning
confidence: 99%
“…In principle, downsizing bulk Si to the nanoscale (below the critical value) can prevent crack propagation due to the reduced strain energy stored from electrochemical reactions, thus improving structural stability and cycling lifespan. Since the pioneering work of Si nanowires as an anode in 2008, a wide range of nanostructures, including hollow nanospheres, nanotubes, and nanosheets, have been explored to avoid mechanical fracture. Furthermore, combining nanostructures with some powerful concepts involving surface coating, void engineering, and compositing (with inactive or conductive medium ) has been demonstrated to be successful in building smart electrode structures, which can achieve exceptional performances with outstanding high specific capacity and long-term cycle life (Figure A). , …”
mentioning
confidence: 99%
“…Figure a–c shows the high-resolution XPS spectra of P 2p, F 1s, and Li 1s in the SEI layer after the first cycle. The Li 1s spectra demonstrate that the Li-containing species on the SEI of SnO 2 /CNFs and P-SnO 2 /CNFs are Li 2 CO 3 , LiF, and ROCO 2 Li, but Li 3 PO 4 can only be found on the P-SnO 2 /CNFs electrode at about 56.4 eV (Figure c). According to the Li 1s spectrum, the content of Li 2 CO 3 in the SEI on the SnO 2 /CNFs reaches 42.6%. The abundance of inorganic components (e.g., Li 2 CO 3 ) in the SEI increases its brittleness .…”
mentioning
confidence: 94%
“…However, the bonding between groups is lost during the heat treatment and only the entanglement of the carbon skeleton exists in the secondary microspheres, resulting in a weak internal connection of the nanosilicon particles. On the other hand, some researchers have found that the poor mechanical properties of carbon shells and the carbonization layer on the silicon surface will catalyze the decomposition of the electrolyte and consume more electrolyte. , Hence, the carbonaceous material after carbonizing is brittle and unable to form a stable solid electrolyte interphase (SEI) film on the surface, and the electrode structure is easy to collapse during the charge–discharge cycles.…”
Section: Introductionmentioning
confidence: 99%